2022
DOI: 10.3389/fcvm.2022.930994
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity predicts therapeutic effects of metoprolol on pediatric postural orthostatic tachycardia syndrome

Abstract: ObjectiveTo determine if the baseline baroreflex sensitivity (BRS) could be a useful predictor for the metoprolol therapeutic efficacy on postural orthostatic tachycardia syndrome (POTS) in children.MethodsIn this retrospective case-control study, 54 children suffering from POTS treated with metoprolol were recruited from the pediatric department of Peking University First Hospital. After 2–3 months of metoprolol treatment, all subjects were divided into responders and non-responders based on whether the sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A high BRS at baseline is associated with a positive therapeutic response to metoprolol, and these findings should help direct the individualized administration of β-adrenoceptor blockers to children with postural tachycardia syndrome (POTS). Cui et al [42] reported that supine BRS was significantly higher in metoprolol responders than in nonresponders. The ROC curve showed that a cutoff value of 8.045 ms/ mmHg predicted the treatment effectiveness for POTS with a sensitivity and specificity of 75.8% and 95.2%, respectively (Table 2).…”
Section: Brs Predicts Response To Metoprolol In Children With Postura...mentioning
confidence: 99%
“…A high BRS at baseline is associated with a positive therapeutic response to metoprolol, and these findings should help direct the individualized administration of β-adrenoceptor blockers to children with postural tachycardia syndrome (POTS). Cui et al [42] reported that supine BRS was significantly higher in metoprolol responders than in nonresponders. The ROC curve showed that a cutoff value of 8.045 ms/ mmHg predicted the treatment effectiveness for POTS with a sensitivity and specificity of 75.8% and 95.2%, respectively (Table 2).…”
Section: Brs Predicts Response To Metoprolol In Children With Postura...mentioning
confidence: 99%